Functional outcomes and patient satisfaction following inpatient treatment for childhood‐onset schizophrenia spectrum disorders vs non‐psychotic disorders in children in the United Kingdom. Issue 2 (20th May 2020) - Galitzer, Hayley; Anagnostopoulou, Nefeli; Alba, Anca; Gaete, Jorge; Dima, Danai; Kyriakopoulos, Marinos
Abstract: Aim: The aim of this study was to compare clinical characteristics and treatment outcomes between children with Childhood‐onset schizophrenia spectrum disorders (COSS) and children with other severe non‐psychotic psychiatric conditions (non‐COSS), all admitted to a national mental health inpatient children's unit. Methods: We conducted a retrospective study of all children discharged from a national children's inpatient unit in the United Kingdom, between 2009 and 2018. We compared functional and treatment outcomes and satisfaction with treatment in COSS with non‐COSS in the whole sample and separately for male and female patients. Results: A total of 211 children (55% boys) were included in the sample. The mean age on admission was 129.7 months (10.8 years; age range, 6‐12).Twenty cases were diagnosed with COSS (9.5%). In the whole sample, COSS patients had significantly lower Children's Global Assessment Scale (CGAS) scores on admission compared to non‐COSS ( P = .006). There was a trend towards children with COSS as a group having a longer admission ( M = 194.6 days, SD = 125.4) compared to non‐COSS ( M = 135.8 days, SD = 86.2), ( P = .053). Females with COSS seemed to have more significant differences compared to females with non‐COSS, in particular, longer admissions ( P = .016) and worse CGAS scores at discharge ( P = .04), whilst in males, these differences seemed to be attenuated. Conclusions: Children with COSS have lower functioning at the point of inpatient admission and possibly longer admissions, but similar satisfaction with treatment at discharge from hospital compared with non‐COSS. Females with COSS may have worse functional outcomes compared to non‐COSS at discharge.